2020
DOI: 10.1111/iwj.13456
|View full text |Cite
|
Sign up to set email alerts
|

Trends in burn injuries in Galicia (Spain): An epidemiological study

Abstract: The treatment of burns is one of the earliest medical activities on record, probably because of the powerful impact of their physical consequences among other sequelae. The aim of the present paper is to perform an epidemiological study of burn patients. The data were obtained by reviewing the medical histories of all those patients admitted or treated in the Outpatients Department of the Burn Unit of our hospital between 2013 and 2017. A sample was gathered of 1401 patients, made up of 716 males (51.11%) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 20 publications
3
5
0
Order By: Relevance
“…An increased incidence rate was found among children and elderly, which corresponds with other studies [ 3 , 10 , 14 , 17 21 ]. The higher incidence rate in children most likely highlights the inability of children to recognize dangers (e.g., hot liquids standing on a table).…”
Section: Discussionsupporting
confidence: 90%
“…An increased incidence rate was found among children and elderly, which corresponds with other studies [ 3 , 10 , 14 , 17 21 ]. The higher incidence rate in children most likely highlights the inability of children to recognize dangers (e.g., hot liquids standing on a table).…”
Section: Discussionsupporting
confidence: 90%
“…Third-degree burns were found in 63.4% of cases in the present analysis, different from other studies in which ≥50% of patients presented second degree burns [ 33 , 35 ]. A report from Albania showed that full-thickness burns affected around 17% of patients [ 31 ], Galicia (Spain) reported 9.5% of cases [ 37 ], Pakistan 33% [ 38 ], and China 40.1% [ 30 ]. This may be a consequence of accumulation of a higher number of severe burn cases per care unit due to the limited number of intensive care beds nationwide dedicated to care of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As for mechanical ventilation, irrespective of the presence or absence of inhalation injuries, it was required in 50.5% of cases. Other studies report a rate of 45.7% [ 32 ] or 6.8% [ 37 ]. Tracheostomy was performed in 7.5% of patients, lower than other reports, such as 15.7% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations